Investors reaction to announcements of acquisition financed by common shares - Taufil Mohd, Kamarun Nisham; Wan Hussin, Wan Nordin; Abdul Latif, Rohaida (Universiti Utara Malaysia, 1995)
The purpose of this paper is to look at the interaction between tightness of ownership and method of payment by the way of common shares offerings on the stock returns of bidding firms in acquisitions. Our results shows that bidding firms earn statistically significant positive abnormal returns and these are directly related to tightness of ownerships.